Spinal Instability in Myogenic Low Back Pain : Stabilization Exercise Approach - Awab Zakie Habibie; M Lutfi Dharmawan; Tertianto Prabowo; Marina A. Moeliono; Lia Amalia Suparyadi (Biomedical Journal of Indonesia, 2024)
Spinal instability can be caused by various conditions including an illness, trauma, and degenerative processes affecting one or more of the three spinal subsystems. These three subsystems are the spine and ligaments, back muscles, and the nervous system work synergistically to maintain spinal stability. Until now it is still difficult to identify spinal instability. Low back pain (LBP) affects 60-80% of the world's population and in the United States causes losses of around $15-50 billion each year. For several decades, a muscle training program has been the main program that recommended to solve LBP, based on the premise that the muscle subsystem is a subsystem that can be repaired and improved, a muscle training program is developed and applied in the management of NPB. This literature review focuses on aspects of stabilization exercises in the management of low back pain with and without spinal instability.